2012
DOI: 10.1093/ejcts/ezs312
|View full text |Cite
|
Sign up to set email alerts
|

Cysteinyl leukotriene receptor antagonist montelukast ameliorates acute lung injury following haemorrhagic shock in rats†

Abstract: The results of the present study reveal that montelukast may ameliorate lung injury in shocked rats by interfering with inflammatory and oxidative pathways, implicating the role of leukotrienes in the pathogenesis of haemorrhagic shock-induced lung inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It is widely used as antiasthmatic therapy for chronic asthma and seasonal allergies with high tolerability in both children and adults [41,42]. It was tested for various pathological conditions as spinal cord injury [43], hippocampal ischemia [44], and hemorrhagic shock [45]. A few years ago, it attracted scientists to be evaluated as a protection for various toxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used as antiasthmatic therapy for chronic asthma and seasonal allergies with high tolerability in both children and adults [41,42]. It was tested for various pathological conditions as spinal cord injury [43], hippocampal ischemia [44], and hemorrhagic shock [45]. A few years ago, it attracted scientists to be evaluated as a protection for various toxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the blockade of CysLTR1 signaling by montelukast attenuated NIHL, even though we posttreated the mice with montelukast after noise exposure. CysLTR1 antagonists such as montelukast and pranlukast have been reported to protect against ischemia/reperfusion injury in a variety of tissues such as in the heart, liver, kidneys, and spinal cord, and the mechanism of these effects was suspected to involve a decrease in inflammation and oxidative stress (25)(26)(27)(28)(29). As inflammation and oxidative stress are also known to contribute to NIHL, we first explored whether montelukast protected against noise-induced cochlear injury through the regulation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, blocking LT pathways may be beneficial in asthma, and this has led to the development of 5-LO enzyme inhibitors (e.g., zileutin) and CysLT1 receptor antagonists (e.g., montelukast, zafirlukast, and pranlukast) (Barnes, 2011;Peters-Golden and Henderson, 2007). Montelukast has been shown to reduce lung inflammation in animal models (Al-Amran et al, 2012). However, recent meta-analyses have shown that corticosteroids are superior for the treatment of chronic and acute asthma, and the role of these agents in the treatment of asthma remains poorly defined (Chauhan and Ducharme, 2012;Watts and Chavasse, 2012).…”
Section: Leukotrienesmentioning
confidence: 99%